The Essential Characteristic of the Concept of «Managerial Competence of the Head of Educational Institution» - Iryna Darmanska (Pedagogical Discourse, 2015)
The article describes the essential characteristic of the concept of «managerial competence of the head of educational institution». The author analyzes the principles and concepts that are the fundamental basis of the formation of a multifaceted system in the management of general secondary education, consisting of interrelated and mutually reinforcing elements. When forming managerial competence of the future managers of educational establishments, scientific and scientific-pedagogical workers should use the researches in the following directions: legal aspects of the educational establishment management, theory of organization of educational establishment, management of organization of educational establishment, labor aspects of activity of the manager of educational establishment, management of educational and upbringing activity, management of financial-economic activity, management of the labor resources, management of the content of work, management of informational links, technique of managerial activity, audit and evaluation of managerial activity, psychology of management, social and economic security of the activity, educational technologies. Methodological basis of the article is the statement of the theory of scientific cognition; system-structural approach, which stipulates for the integrity of the object’s study, finding the specificity of its components; statement of the interaction of the subjects, their functional interconnection, which allows to study the subject as one whole.